Changes in psychiatry residents' attitudes towards individuals with substance use disorders over the course of residency training. (17th October 2016) - Avery, Jonathan; Han, Bernadine H.; Zerbo, Erin; Wu, Guojiao; Mauer, Elizabeth; Avery, Joseph; Ross, Stephen; Penzner, Julie B.
Abstract : Background and Objectives: Psychiatry residents provide care for individuals diagnosed with co‐occurring mental illness and substance use disorders (SUDs). Small studies have shown that clinicians in general possess negative attitudes towards these dually diagnosed individuals. This is a serious concern, as clinicians' stigmatizing attitudes towards individuals with mental illnesses may have a particularly potent adverse impact on treatment. The goal of this study was to examine the attitudes of psychiatry residents towards individuals with diagnoses of schizophrenia, multiple SUDs, co‐occurring schizophrenia and SUDs, and major depressive disorder. Methods: A questionnaire was sent to psychiatry residents ( N  = 159) around the country. It was comprised of two sections: (i) demographic information, which included information about level of training; and (ii) the 11‐item Medical Condition Regard Scale (MCRS) for individuals with the four different diagnoses. Results: Psychiatry residents had more stigmatizing attitudes towards individuals with diagnoses of SUDs with and without schizophrenia than towards those individuals with diagnoses of schizophrenia or major depressive disorder alone. Senior residents possessed more negative attitudes towards individuals with SUDs than junior residents. Discussion and Conclusions: The attitudes of psychiatry residents' towards individuals with SUDs with and without schizophrenia were negative and were worse among senior residents. There were many potential reasons for these findings, including repeat negative experiences in providing care for these individuals. Scientific Significance: The negative attitudes of psychiatry residents towards individuals with SUDs are worrisome. Future work is needed to better understand these attitudes and to develop interventions to improve them. (Am J Addict 2017;26:75–79)